In vivo exposure to bisphenol F induces oxidative testicular toxicity: role of Erβ and p53/Bcl-2 signaling pathway - Odetayo, Adeyemi Fatai; Adeyemi, Wale Johnson; Olayaki, Luqman Aribidesi (Frontiers in Reproductive Health, 2023)
Introduction Bisphenol F (BPF), an alternative to bisphenol A has been implicated as a gonadotoxic substance. BPF has been shown to induce hormonal imbalance and testicular oxidative damage. However, the mechanism associated with BPF-induced testicular toxicity has not been fully explored. This study was designed to explore the role of tumor protein (p53)/ B-cell lymphoma 2 (BCl-2) signaling and oestrogen receptor beta (Erβ) in BPF-induced testicular toxicity. Methods Male Wistar rats were randomized into control (Cntrl), BPF-treated (10, 30, and 50 mg/kg for low dose (BPF-L), medium dose (BPF-M), and high dose (BPF-H) respectively), and BPF-treated recovery (Cntrl-R, BPF-L-R, BPF-M-R, and BPF-H-R). The administration was via gavage and lasted for 28 days and the animals in the recovery groups were allowed 28-days exposure free period for recovery from BPF exposure. Results BPF resulted in the distortion of the testicular histoarchitecture, which was accompanied by a significant rise in testicular gamma-lutamyl transferase and lactate dehydrogenase activities but a decline in sorbitol dehydrogenase activities. Also, BPF caused a significant reduction in plasma gonadotropin-releasing hormone, luteinising hormone, follicle-stimulating hormone, and testosterone, which was associated with the downregulation of testicular 3beta-hydroxysteroid dehydrogenase and 17beta-hydroxysteroid dehydrogenase activities. Furthermore, BPF induced testicular inflammation, redox imbalance, and apoptosis, accompanied by distortion in p53/BCl-2 signaling and overexpression of Erβ. Again, the observed toxic effects of BPF were dose-dependent and not completely reversed by BPF cessation. Discussion Bisphenol F induced gonadotoxicity by distorting p53/BCl2 signaling and the expression of Erβ. These observed alterations were not completely reversed after the cessation of BPF exposure.